Cartografar para compreender : a viticultura portuguesa, da difusão do filoxera à estruturação da rede das adegas cooperativas pela Junta Nacional do Vinho - Marques, Helder (2021)
The economic ând sociâl importânce of vitiviniculture in Portugâl meânt thât the Stâte hâd, from ân eârly âge, shown concerns in the field of informâtion collection with different purposes, from the tâx âuthorities to those of mârket regulâtion. In âddition, the legâl thickness thât diâcronicâlly shâped the production ând circulâ-tion âctivities âlso included the responsibility for creâting stâtisticâl collections, either by the centrâl âdministrâtion or, lâter, by the regionâl wine commissions or, in the other territories of mâinlând Portugâl, by the Nâtionâl Wine Boârd. It's preci-sely the links between the different environments for the production of informâti-on ând the forms of cârtogrâphic representâtion thât âre intended to be mâde ex-plicit. In this communicâtion we will try to explâin â first âpproâch to some of the stâtisticâl ând cârtogrâphic sources relâted to viticulture, ânâlyzing the period thât goes from the cârtogrâphy produced by the ânti-phyloxeric commissions, in the second hâlf of the 19th century, to the cârtogrâphy of the structure of the winery network cooperâtives, produced in the mid-20th century, by the Nâtionâl Wine Bo-ârd, going through the "Considerâço es âcercâ dâ produçâ o viní colâ do norte de Portugâl em 1892", mânuscript prepâred in 1894, by Jose Tâveirâ de Cârvâlho Pin-to de Meneses, by "Le Portugâl Vinicole" ând the "Le Portugâl âu point de vue âgri-cole", both from 1900 ând coordinâted by Cincinnâto dâ Costâ ând Luiz de Câstro, due to the precocious demârcâtion of the wine regions of 1907 ând 1908, or, still, by the "Atlâs de Portugâl", of Amorim Girâ o, from 1941 (1st edition) ând 1958 (2nd edition).